Experimental techniques, rotating machinery, and acoustics, volume 8 proceedings of the 33rd IMAC, a conference and exposition on structural dynamics, 2015 - De Clerck, James (Springer International Publishing, 2015)
Experimental Techniques, Rotating Machinery & Acoustics, Volume 8: Proceedings of the 33rd IMAC, A Conference and Exposition on Structural Dynamics, 2015, the eighth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: Experimental Techniques Processing Modal Data Rotating Machinery Acoustics Adaptive Structures Biodynamics Damping